An effective method of forming the professional orientation of future chemistry teachers in the context of distance education (Journal of Educational Sciences, 2021)
Today, conceptually, in the conditions of the education system: digitalization of the educational process, digital educational content, digitalization of education management, the formation of the pro- fessional orientation of the future chemistry teacher is of great importance. Despite the rapid spread of covid-19 in the world, one of the ways to maintain the position of the state program “Digital Kazakhstan” and “new development opportunities in the conditions of the Fourth Industrial Revolution”, the national idea “Mangilik El” is to increase the effectiveness of the distance education process. The spread of the epidemic in the world and in the country has shown that distance education needs to be given more attention. The main purpose of this study is to determine the value of digital educational resources as an effective method of forming the professional orientation of future chemistry teachers. The study used theoretical (analysis, generalization, comparison, synthesis of philosophical, psychological, pedagogical and scientific-methodological literature); empirical (survey, conversation) methods. As a result of the research, the significance of the process of digitalization of education in the formation of professional orientation of future chemistry teachers in the conditions of distance education is determined. The results of the study are useful to use in higher education institutions in the process of professional training of future teachers, improving their professional skills, distance learning and in institutes of advanced train- ing of teachers.Key words: distance education, future chemistry teacher, career guidance, teaching method, digital resources, research methods, research direction, innovation.